Anthropogenic calling sites boost the sound amplitude of advertisement calls produced by a tropical cricket. (August 2018) - Erregger, Bettina; Schmidt, Arne K.D.
Abstract : Acoustic signals are widely used as sexual displays to attract mates. The choice of display site can strongly influence the male call characteristics and their attractiveness to females. Males can improve the conspicuousness of their signals by increasing sound amplitude and expanding their broadcast area thereby reaching more potential mating partners and influencing female choice. Insects possess a rather limited degree of signal plasticity. To increase the intensity of their calls, insects have been known to manipulate and engineer their display locations. Mole crickets, for example, build burrows that are shaped like horns, designing the burrow such that its resonance closely matches that of their call frequency, thereby boosting sound amplitude. Tree crickets manipulate plant leaves, using them as baffles for optimal sound radiation. In this study, we show for the first time that an insect species can enhance its advertisement calls by using novel, anthropogenic environments as singing sites. During this study, the tropical cricket Anurogryllus muticus was frequently found singing beside the walls of houses, on concrete stairs or in storm drains. These locations significantly increased the sound amplitude of its calls, by an average of 13 and 7 dB SPL, respectively, as measured above and in front of the singing animals compared to the sound amplitude measured in their natural grassland habitat. To evaluate the effect of calling site choice on the male's life span, we conducted a 35-day population survey using the mark and recapture method. Our results revealed that those males that called in grassland habitat without occupying burrows had the shortest minimum life spans. Highlights: Tropical crickets use anthropogenic objects as calling sites. Males calling on anthropogenic objects show a considerably increased sound amplitude. Louder calls lead to an increased active space and attract more females. Males calling on grassland without burrows had the lowest minimum life span.